Contextualising Research: A Study about Women Entrepreneurs in Brazil - Prieto, Nathalia (2013)
This research explores the Brazilian context, responding to the extensive critique that entrepreneurship is predominantly focused on the U.S and Europe (e.g. Tedmanson et al. 2012; Bruton et al. 2008). It considers the entrepreneur as an actor embedded in social surroundings (Spedale and Watson 2013), which can either facilitate or constrain the entrepreneurial action (Welter 2011). To investigate that, the focus is narrowed to Brazilian women entrepreneurs. Particularly, it explores how women perceive entrepreneurship in Brazil as a patriarchal country (Caulfield 2011) with gender inequalities (William and Youseff 2013; Hausmann et al. 2012). Similarly, the gender topic is also under explored outside developed countries (Ahl and Marlow 2012; Ahl 2006). To conduct the research, an interpretivist, qualitative approach and a discourse analysis method were used (Bryman 2012; Silverman 2011). Initially, 48 Brazilian women presently owning or developing businesses were questioned through an online survey. Additionally, 9 from these respondents were selected to a semi-structured interview. The findings were analysed and presented through a thematic approach (Braun and Clarke 2006). It was found that Brazil incentives entrepreneurship at institutional and social level. However, the context’s bureaucracy, poor qualified support and unsuitable infrastructure are perceived as high constrains. In the gender aspect, the notion of entrepreneurship embedded in a male discourse (Ahl 2006) was found to be still present. The patriarchal aspect (Caulfield 2001) was mostly observed in the association of the female role with the household and children care, both within academia (Ferreira et al. 2012) and practice (Greco 2012). Nevertheless, contrary to these assumptions, this research found that women do not necessarily invest in entrepreneurship due to household or family issues. Overall, this research concludes that women in Brazil are incentivised to pursue entrepreneurship as a career; however, they may face obstacles due to gendered bias practices and discourses. Therefore, this research critiques the local academic production and practice regarding its assumption of female entrepreneurship, offering new insights. Additionally, it hopes to provide a perspective of how public policies could be improved towards reducing the obstacles to entrepreneurship.